Experimental measurement of graphite wear in helium at elevated temperatures and the discrete element modelling of graphite dust production inside the Pebble Bed Modular Reactor - Wilke, Charel Daniel (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.